Relationship between quality management practices and innovation - Kim, Dong‐Young; Kumar, Vinod; Kumar, Uma (Journal of Operations Management, 2012)
AbstractThe purpose of this study is to examine the associations among different quality management (QM) practices and investigate which QM practices directly or indirectly relate to five types of innovation: radical product, radical process, incremental product, incremental process, and administrative innovation. We test the proposed framework and hypotheses using empirical data from ISO 9001 certified manufacturing and service firms. The results show that a set of QM practices through process management has a positive relationship with all of these five types of innovation. It was found that process management directly and positively relates to incremental, radical, and administrative innovation. Organizational capability to manage processes may play a vital role in identifying routines, establishing a learning base, and supporting innovative activities. The findings also reveal that the value of an individual QM practice is tied to other QM practices. Therefore, highlighting just one or a few QM practices or techniques may not result in creative problem solving and innovation.